The Effectiveness of an Instructional Guide on Chinese Pre-Service EFL Teachers’ Knowledge in Teaching Phonics - Minjie, Chen; Hock Seng, Goh; Ruey Shing, Soo; Guojie, Yin (Department of English Education, Faculty of Teacher Training and Education, Universitas Syiah Kuala, Banda Aceh, Indonesia., 2022)
In China, phonics instruction has been given substantial emphasis ever since the implementation of the 2011 National English Curriculum for Compulsory Education. However, many Chinese students’ learning outcome remains unsatisfactory due to EFL teachers’ insufficient knowledge to teach phonics and the absence of a phonics instructional guide. To address this gap, this study aims to investigate the effects of a newly developed phonics instructional guide on Chinese pre-service EFL teachers’ knowledge base to teach phonics. Adopting an experimental research design, the study was conducted at a teachers’ college in Sichuan Province, China. There were 172 pre-service EFL teachers assigned into two equivalent groups, namely the experimental group (N=86) and control group (N=86), who took a test respectively before and after the intervention. The measures of the test included seven dimensions aiming to elicit knowledge of general phonics, phonetic system, phonemic awareness, phonics decoding rules, phonics instructions, reinforcement methods, and sight word instructions. The experimental group participants.